A função parental masculina na perspectiva de um bisavô - Loureiro, Renata Costa Rolim (2009)
The present research aims to describe how a senior male, who lived in the 20th century, passing by all the stages of his life cycle, signified the parental function, inserted in a social context of changes, in which, little years ago, the patriarchal model was used to establish the relation between father and son, determined by remote friendship, in a society in which the life expectancy decreased and do not give to the individual the opportunity of living all the stages of the male parental function. These research included the report of the life biography of a man aged 80, of high middle class backgrounds, living in city and drawn from a non clinical population. The theoretical approaches which formed the basis for the conceptual framework of this investigation was: studies on masculinity and the gender perspective, Bioecological perspective of development and life cycle. The results show that besides the contemporary division of the life cycle in different stages, the biography of this individual only unveil three phases, and the transition of each one are influenced of word. Besides, it is possible to observe that the individual is influenced by a social context of changes, make signification an negotiation in his way of looking after, not based on the patriarchal model learned by his father and grandfather. At the same way, the individual remains his authority and position in the family